PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA PT. KARYA MEKAR DEWATAMALI - Fauzhatul Jannah, Rizky; Anah, Lik (Perwira Journal of Economics & Business, 2025)
The study intended to explore how job satisfaction and organizational commitment affect organizational citizenship behavior (OCB) at PT. Karya Mekar Dewatamali. A total of 194 employees were included in the research population at PT. Karya Mekar Dewatamali, and 49 employees were selected as the sample using incidental sampling. The research was based on a quantitative approach. Data processing included descriptive statistics, data quality testing (including vailidity and reliability tests), classical assumption testing (including normality, multicollinearity, and heteroscedasticity tests), multiple linear regression analysis, and hypothesis testing. The results of these findings include the following: (1) job satisfaction has a significant and positive relationship with organizational citizenship behavior (OCB) at PT. Karya Mekar Dewatamali. (2) Organizational commitment has a significant and positive relationship with OCB at PT. Karya Mekar Dewatamali. Third, job satisfaction and organizational commitment have a significant, positive relationship with OCB at PT. Karya Mekar Dewatamali.